2014
DOI: 10.1007/s11356-014-3249-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant roots on the hydraulic performance during the clogging process in mesocosm vertical flow constructed wetlands

Abstract: The aim of this study was to evaluate the effects of plant roots (Typha angustifolia roots) on the hydraulic performance during the clogging process from the perspective of time and space distributions in mesocosm vertical flow-constructed wetlands with coarse sand matrix. For this purpose, a pair of lab-scale experiments was conducted to compare planted and unplanted systems by measuring the effective porosity and hydraulic conductivity of the substrate within different operation periods. Furthermore, the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 44 publications
1
6
0
4
Order By: Relevance
“…As a result of this drying episode, the following months showed an abnormal behavior for the BOD 5 value, a circumstance that can be related to the possible formation of preferential flow paths in the HF-CW bed that would have decreased the HRT. Other authors reported that an excessive root growth may cause the unbundling of the bed, encourage the creation of preferred paths and short circuits and open new pore spaces in the substrate [30,33]. From December 2013, a tendency to return to the proper working order of the CW was observed.…”
Section: Abatement Of Organic Mattermentioning
confidence: 98%
“…As a result of this drying episode, the following months showed an abnormal behavior for the BOD 5 value, a circumstance that can be related to the possible formation of preferential flow paths in the HF-CW bed that would have decreased the HRT. Other authors reported that an excessive root growth may cause the unbundling of the bed, encourage the creation of preferred paths and short circuits and open new pore spaces in the substrate [30,33]. From December 2013, a tendency to return to the proper working order of the CW was observed.…”
Section: Abatement Of Organic Mattermentioning
confidence: 98%
“…Quanto à remoção de demanda bioquímica de oxigênio (DBO) e de sólidos suspensos totais (SST), não se constatou diferença entre os SACs (p>0, 05), no entanto a eficiência de remoção de demanda química de oxigênio (DQO) foi diferente entre os SACs orgânica, mineralização de nutrientes e remoção de patógenos, bem como funcionam como intermediárias em processos físicos e químicos como filtração, adsorção, precipitação e sedimentação (BRIX, 1994;1997;BIAŁOWIEC;JANCZUKOWICZ;RANDERSON, 2011;SHELEF;GROSS;RACHMILEVITCH, 2013). Apesar de controvérsias, autores como Hua et al (2014) e Matos et al (2015), entre outros, têm demonstrado que a planta e seu sistema radicular também contribuem para o aumento do tempo de vida útil das unidades, pela atenuação do progressivo processo de obstrução do meio poroso.…”
Section: Introductionunclassified
“…-deposition of the particles (Batchelor and Loots 1996;Sani et al 2013;Knowles and Davies 2011), -microbial biomass activity (Tanner and Sukias 1995;Sani et al 2013), -root density and condition (Breen and Chick 1995;Hua et al 2014), -mechanical compaction of filter media (Winter and Goetz 2003), -chemical precipitation (Winter and Goetz 2003), and -gas blocking (Langergraber et al 2003).…”
Section: Introductionmentioning
confidence: 99%